Faktor Yang Berhubungan Dengan Gangguan Siklus Menstruasi Pada Mahasiswi Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia - Mildha Afiyah Salsabila; Sumiaty; Andi Surahman Batara (Window of Public Health Journal, 2026)
Health is an important aspect of human life, and a balanced diet is essential to achieving it. Currently, the increasing consumption of fast food has become a phenomenon that negatively impacts health, including women's menstrual cycles. This study aims to determine the factors associated with menstrual cycle disorders in female students of the Faculty of Public Health, Muslim University of Indonesia, in 2025. This study uses a quantitative, cross-sectional design. The population in this study comprised 171 female students, and a sample of 120 was selected using a random sampling technique based on the Slovin Formula. Data were collected through questionnaires and observations and then analyzed using the chi-square test. The results showed that the frequency of fast food consumption (p = 0.004; p < 0.05) and stress (p = 0.002; p < 0.05) were factors associated with menstrual cycle disorders. Physical activity (p = 0.876; p > 0.05) was not a factor associated with menstrual cycle disorders. It is hoped that future researchers will reconsider factors that may be related to menstrual disorders and add other variables that have not been studied (e.g., sleep, caffeine consumption, hormonal factors) to refine this research further and yield more in-depth, optimal results.